1979
DOI: 10.1007/bf00266320
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of injuries to the menisci of the knee joint

Abstract: Direct methods were used to determine the distribution of injuries to the menisci in formalin fixed knee joints, rotated under physiological pressures when extended and at different degrees of flexion. The position of the joint during rotation rather than the direction of rotation determined the distribution of injury between the menisci, whereas both direction of rotation and joint position determined the position of major types of lesion within the meniscus. Support is given for the view that the incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It was shown in an in vitro study that tibio‐femoral compression in conjunction with forceful flexion and torsion of the knee can cause vertical‐longitudinal lesions [16]. The knees were twisted maximally in this study, while we used only a moderate torque.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown in an in vitro study that tibio‐femoral compression in conjunction with forceful flexion and torsion of the knee can cause vertical‐longitudinal lesions [16]. The knees were twisted maximally in this study, while we used only a moderate torque.…”
Section: Discussionmentioning
confidence: 99%
“…Ishibashi 20) showed that ascent from a squat was a risk factor for knee osteoarthritis in Japanese. Another report has shown that meniscal injuries may occur when the knee is subject to rotation under physiological pressure during deep knee flexion 21) . Such movement during knee flexion may cause damage to both the meniscus and the cartilage in the femorotibial joint.…”
Section: Discussionmentioning
confidence: 99%
“…According to clinical studies on patients with knee osteoarthritis in Japan, it would appear that the movement of the menisci in deep knee flexion may have a bearing on meniscal injuries, and that those injuries themselves may be followed by knee osteoarthritis [17][18][19][20][21] . Therefore, we believe it is important to investigate the mechanism involved in the movement of the menisci during deep knee flexion in normal persons.…”
Section: Introductionmentioning
confidence: 99%